Alterations, Interactions, and Diagnostic Potential of Gut Bacteria and Viruses in Colorectal Cancer - Gao, Renyuan; Zhu, Yefei; Kong, Cheng; Xia, Kai; Li, Hao; Zhu, Yin; Zhang, Xiaohui; Liu, Yongqiang; Zhong, Hui; Yang, Rong; Chen, Chunqiu; Qin, Nan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Gut microbiome alteration was closely associated with colorectal cancer (CRC). Previous studies had demonstrated the bacteria composition changes but lacked virome profiles, trans-kindom interactions, and reliable diagnostic model explorations in CRC. Hence, we performed metagenomic sequencing to investigate the gut microbiome and microbial interactions in adenoma and CRC patients. We found the decreased microbial diversity in CRC and revealed the taxonomic alterations of bacteria and viruses were highly associated with CRC at the species level. The relative abundance of oral-derived species such as Fusobacterium nucleatum, Fusobacterium hwasookii, Porphyromonas gingivalis, and Bacteroides fragilis increased. At the same time, butyrate-producing and anti-inflammatory microbes decreased in adenoma and CRC by non-parametric Kruskal-Wallis test. Despite that, the relative abundance of Escherichia viruses and Salmonella viruses increased, whereas some phages, including Enterobacteria phages and Uncultured crAssphage, decreased along with CRC development. Gut bacteria was negatively associated with viruses in CRC and healthy control by correlation analysis (P=0.017 and 0.002, respectively). Viruses were much more dynamic than the bacteria as the disease progressed, and the altered microbial interactions were distinctively stage-dependent. The degree centrality of microbial interactions decreased while closeness centrality increased along with the adenoma to cancer development. Uncultured crAssphage was the key bacteriophage that enriched in healthy controls and positively associated with butyrate-producing bacteria. Diagnostic tests based on bacteria by random forest confirmed in independent cohorts showed better performance than viruses for CRC. In conclusion, our study revealed the novel CRC-associated bacteria and viruses that exhibited specific differences and intensive microbial correlations, which provided a reliable diagnostic panel for CRC.